Proceso de atención de enfermería en paciente adulto mayor de 65 años con pancreatitis aguda. - Morales Suarez, Mercedes María (2020)
Introduction Acute pancreatitis is an acute inflammatory process of the pancreas, which has recently been diffuse, presenting a variable level of glandular involvement of proximal retoperitoneal tissues and other distal organs. Where pancreatic enzymes are activated in the light of the duodenum; that is, they are activated within the acynes by pancreatic enzymes and are released from the pancreatic ducts, causing pancreatic inflammation. Objective To apply the Nursing Care process to an adult patient over 65 with acute pancreatitis to recover health in a comprehensive and efficient way. Clinical case the objective of this clinical case is to disseminate the Nursing Care Process in an adult over 65 years of age with acute pancreatitis. The study includes studies of computed tomography of abdomen, chest X-ray, hematological analysis. Conclusion: The Nursing Interventions were planned, executed and evaluated with quality and warmth, according to the patient's profile, the findings of amylase and very high lipase were the trigger for the process of inflammation of the pancreas, the treatment was; intravenous hydration, analgesics, nothing by mouth very crucial within 48 - 72 hours, the communication of the nurse / patient, doctor, facilitates rapid recovery of the patient, the Intensive Care Unit, is the ideal room for recovery of patients with pancreatitis sharp.